Log-Convex Polynomial Approximation in Log. of Twice Differentiable Functions - Darwesh, Halgwrd Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2008)
In this paper, we introduce a new concept of constrained approximation, which we call Log-convex polynomial approximation in log. We obtained a direct theorem of log-convex polynomial approximation in log for twice differentiable functions on [-1, 1], in term of the ordinary moduli of continuity. Keywords: Shape preserving approximation, convex and log-convex functions, Splines, moduli of continuity and smoothness.